A key to the corticolous microfoliose, foliose and related crustose lichens from Rondônia, Brazil, with the description of four new species. (23rd October 2014) - APTROOT, André; CÁCERES, Marcela Eugenia da Silva
Abstract A key is given to the foliose and squamulose lichens known so far from Rondônia, including also corticolous crustose lichens with a chlorococcoid alga. The foliicolous Lecanorales found are also listed. The following four new corticolous Lecanorales are described from Rondônia: Calopadia granulosa with a granular, corticate thallus and ascospores 1 per ascus, 33–38×10·5–13·0 µm; Crustospathula amazonica with irregularly capitate to nearly globose, c. 0·2–0·4 mm diam. soralia on cartilaginous stalks; Flavoparmelia plicata with a thallus containing usnic and protocetraric acids, with laminal, irregular, globose to cylindrical isidia which are often easily abraded and showing the whitish medulla, but not sorediate or postulate; Physcidia striata with ascending squamules, without hypothallus, often with laminal isidia in defined areas towards lobe tips of some, usually sterile lobes, and often with biatorine apothecia with ascospores simple to 1-septate, (6·2–)7·5–10·0×(2·5–)3·0–3·5 µm. In the whole lichen flora of the lowland rainforest region of Rondônia, the following traits can be discerned: foliose lichens amount to only 17 species (2·7% of nearly 600), 33 (5·5%) are squamulose, while the vast majority (91·8%) are crustose. Cyanobacteria are present in only 6 (1%) species. A chlorococcoid alga present in c. 100 (16%), 12 of which (2%) have a myrmecioid alga. The remainder of the species, a staggering 83%, have trentepohlioid alga, including 6 (1%) with Phycopeltis. In neotropical lowland rainforest, the vast majority of the lichens are crustose and contain a trentepohlioid alga, and the Arthoniales, Graphidaceae and pyrenocarpous lichens are the main groups, each accounting for roughly a quarter of the lichen biodiversity.